Reviewer Acknowledgements for the Special Edition at Global Health Management Journal: The 1st Special Edition of Cirebon International Health Symposium - GHMJ (Global Health Management Journal) (GHMJ (Global Health Management Journal), 2024)
Of more than 100 papers selected by the internal committees of the 1st Cirebon International Health Symposium, organized by Faculty of Medicine, Universitas Swadaya Gunung Jati, there are 24 papers will be featured in the 1st Special Edition of the Symposium, and published in GHMJ (Global Health Management Journal), Vol. 7, No.4, 2024 of the journal. GHMJ (Global Health Management Journal) wishes to acknowledge the following scholars and professionals for their invaluable support in reviewing the manuscripts for this issue. Their dedication and expertise have been instrumental in upholding the journal's quality, and we deeply appreciate the contributions. The papers published in this Special Edition have been double-blind peer-reviewed by the Editorial Board of Global Health Management Journal, and the internal or external reviewer. Editor-in-chief Prof. Andrew John Macnab Managing Editor Doni Marisi Sinaga, M.Sc. Internal Reviewers from Faculty of Medicine, Universitas Swadaya Gunung Jati, Indonesia Donny Nauphar, M.Si.Med Uswatun Khasanah, M.Pd., MKM. Ahmad Fariz Malvi Zamzam Zein, Sp.PD, FINASIM, MM, FACP Ariestya Indah Permata Sari, Ph.D Bambang Wibisono, MH Tiar M. Pratamawati, MM, M.Biomed Tissa Octavira Permatasari, M.MedEd Witri Pratiwi, M.Kes. Vivi Meidianawaty, M.MedEd External Reviewers Antarini, M.Kes. (Pangkalpinang Health Polytechnic, Indonesia) Ratih Yulistika Utami, MMedEd (Universitas Muhammadiyah Sumatera, Indonesia) Bayu Mitra Adhyatma Kusuma M.AP., M.Pol.Sc. (National Dong Hwa University, Taiwan) Nethnapa Vongskan, PhD. (Shinnawatra University, Thailand) Supim Wongtongtair, Ph.D. (Srinakharinwirot University, Thailand) Sarah Jane Lubaton Racal, Ph.D. (Christian University of Thailand) Sunna Vyatra Hutagalung, Ph.D. (Universitas Sumatera Utara, Indonesia) GHMJ (Global Health Management Journal) is recruiting reviewers for the journal. If you are interested in becoming a reviewer, we welcome you to join us. Please register at our website and indicate as Reviewer. Benefits of Joining:* Your name will be listed in the journal as a Reviewer for each edition you contribute to.* You will be invited to join the Editorial Board for future editions, offering further opportunities for professional development.* As a special privilege, reviewers will have the chance to publish Editorial Papers with us free of charge.   Published: 21 November 2024